Affective meditation and the invention of medieval compassion - McNamer, Sarah (The middle ages series, 2010)
Intimate scripts in the history of emotion -- Compassion and the making of a true Sponsa Christi -- The genealogy of a genre -- Franciscan meditation reconsidered -- Feeling like a woman -- Marian lament and the rise of a vernacular ethics -- Kyndenesse and resistance in the Middle English passion lyric